2019
DOI: 10.1093/ajcn/nqy216
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns before and during pregnancy and maternal outcomes: a systematic review

Abstract: Background Hypertensive disorders of pregnancy (HDP) and gestational diabetes mellitus (GDM) are common maternal complications during pregnancy, with short- and long-term sequelae for both mothers and children. Objective Two systematic review questions were used to examine the relation between 1) dietary patterns before and during pregnancy, 2) HDP, and 3) GDM. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 72 publications
3
58
0
2
Order By: Relevance
“…Other studies reported that unhealthy dietary patterns or lowmixed diets (lack of non-vegetarian diet or fruits or pulses) are associated with adverse pregnancy and birth outcomes like gestational hypertension, pre-term delivery, gestational diabetes mellitus, etc. (47,48). Maternal diet during pregnancy has a significant impact on the levels of fatty acids in erythrocytes and breast milk.…”
Section: Importance Of the Studymentioning
confidence: 99%
“…Other studies reported that unhealthy dietary patterns or lowmixed diets (lack of non-vegetarian diet or fruits or pulses) are associated with adverse pregnancy and birth outcomes like gestational hypertension, pre-term delivery, gestational diabetes mellitus, etc. (47,48). Maternal diet during pregnancy has a significant impact on the levels of fatty acids in erythrocytes and breast milk.…”
Section: Importance Of the Studymentioning
confidence: 99%
“…However, it is only recently that dietary pattern analyses are being used to study the maternal diet during pregnancy. Most data available are from high-income countries with Raghavan et al [17], indicating that the majority of research available is from healthy Caucasian women with access to medical care. Kibret et al [18] concluded that research in low-income countries is needed to comprehend the impact of restricted resources on maternal dietary intake.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy has been identified as a teachable moment [ 2 ], when women may be motivated to make lifestyle changes to improve their own health and the health of their unborn baby. Encouraging women to improve their diet and levels of physical activity is beneficial for not only supporting healthy gestational weight gain (GWG) and maternal health [ 3 ] but also developing behaviors that may potentially improve the health of the whole family.…”
Section: Introductionmentioning
confidence: 99%